Lealtà istituzionale, fedeltà religiosa e integrità morale in democrazia (Stato, Chiese e pluralismo confessionale, 2023)
Institutional loyalty, religious fidelity and moral integrity in a democracyABSTRACT: The deontological and contractualist ethical approach in support of democracy has limits because it does not respect personal moral autonomy. This does not allow the single person to be loyal to public institutions, faithful to religion and morally consistent. Therefore, a consequentialist approach to the rules is proposed.SOMMARIO: 1. Democrazia e religione - 2. Laicità e libertà - 3. Ragione e morale.